2-AG-loaded and bone marrow-targeted PCL nanoparticles as nanoplatforms for hematopoietic cell line mobilization - Sevil Köse; Cem Varan; Selin Önen; Emirhan Nemutlu; Erem Bilensoy; Petek Korkusuz (Stem Cell Research & Therapy, 2024)
Abstract Background The use of mobilizing agents for hematopoietic stem cell (HSC) transplantation is insufficient for an increasing number of patients. We previously reported lipid made endocannabinoid (eCB) ligands act on the human bone marrow (hBM) HSC migration in vitro, lacking long term stability to be therapeutic candidate. In this study, we hypothesized if a novel 2-AG-loaded polycaprolactone (PCL)-based nanoparticle delivery system that actively targets BM via phosphatidylserine (Ps) can be generated and validated. Methods PCL nanoparticles were prepared by using the emulsion evaporation method and characterized by Zetasizer and scanning electron microscopy (SEM). The encapsulation efficiency and release profile of 2-AG were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS). The presence of cannabinoid receptors (CBRs) in HSCs and monocytes was detected by flow cytometry. Cell morphology and viability were assessed using transmission electron microscopy (TEM), SEM, and the WST-1 viability assay. The migration efficacy of the 2-AG and 2-AG-loaded nanoparticle delivery system on HSCs and HPSCs (TF-1a and TF-1) and monocytes (THP-1) was evaluated using a transwell migration assay. Results The 140–225 nm PCL nanoparticles exhibited an increasing polydispersity index (PDI) after the addition of Ps and 2-AG, with a surface charge ranging from − 25 to -50 mV. The nanoparticles released up to 36% of 2-AG within the first 8 h. The 2-AG-Ps-PCL did not affect cellular viability compared to control on days 5 and 10. The HSCs and monocytes expressed CB1R and CB2R and revealed increased migration to media containing 1 µM 2-AG-Ps-PCL compared to control. The migration rate of the HSCs toward monocytes incubated with 1 µM 2-AG-Ps-PCL was higher than that of the monocytes of control. The 2-AG-Ps-PCL formulation provided a real time mobilization efficacy at 1 µM dose and 8 h time window via a specific CBR agonism. Conclusion The newly generated and validated 2-AG-loaded PCL nanoparticle delivery system can serve as a stable, long lasting, targeted mobilization agent for HSCs and as a candidate therapeutic to be included in HSC transplantation (HSCT) protocols following scale-up in vivo preclinical and subsequent clinical trials. Graphical Abstract